Design and Analysis of IMC based Load Frequency Controller for NMP - Hydro Turbine Power System - Ms.Supriya Y. Bhuran, Mr.Sharad P. Jadhav (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Electricity is essential for human life. Literature review shows that power grid failure may cause blackout; many people get affected due to these blackouts. For power generation, different turbines are used viz. steam turbine, gas turbine, hydro turbine, etc. Load Frequency Control (LFC) or automatic generation control is a very crucial parameter in power system control that needs to be tackled. It is observed that traditional controllers like PID controllers and soft computing-based controllers are designed to address the problem faced by most of the power systems. Literature indicated that there is scope to design an efficient and advanced controller for such a critical power system. This paper is a sincere attempt to design and analysis of IMC based controller for a nonminimum phase behaviour type hydro turbine power system. The performance of the designed IMC controller for load change scenarios is presented. Simulation results show the efficacy of the IMC controller and are one of the good options for a non-minimum phase (NMP) hydro turbine power system(HTPS).